THE RELATIONSHIP OF REPRODUCTIVE HEALTH KNOWLEDGE WITH THE INCIDENCE OF PRURITUS VULVAE IN ADOLESCENT GIRLS AGE 13-15 YEARS - Amelinda, Qoriroh Putri; Kustin; Nafista, Ulfia Fitriani (Journal of Nursing Periodic, 2025)
Background: Around the world, adolescent girls often experience problems with their reproductive system, one of which is Pruritus Vulvae. According to the Indonesian Ministry of Health, as many as 5.2 million adolescent girls often experience this condition, and the lack of knowledge of adolescents about reproductive hygiene is one of the causes of this problem. Purpose: This study aims to determine the relationship between reproductive health knowledge and the incidence of pruritus vulvae at SMP Negeri 3 Panji. Methods: This research belongs to the type of quantitative research. The research design uses a correlational descriptive with a cross-sectional approach. There were 90 respondents present in the study and samples used as many as 84 respondents using the Proportionate Stratified Random Sampling technique. The instruments used are questionnaires related to knowledge of reproductive health and Pruritus Vulvae. The questionnaire has been tested for validity and rehabilitation. Data analyzed using the Spearman test. Results: From the results of the univariate analysis showed that 45 (53,57%) respondents have high knowledge, 34 (40,48%) respondent have moderate knowledge, and respondent has low knowledge 5 (5,95%). As well as 66 (78,57%) respondents do not have Pruritus Vulvae and 18 (21,43%) respondants have pruritus vulvae. The result of bivariat analysis obtained p-value (0,012) ≤ α (0,05), that there is a relationship of knowledge of reproductive health with the occurrence of Priritus Vulvae. Conclusions: The majority of Panji high school pupils have high knowledge of reproductive health and do not experience Pruritus Vulvae. So it can be concluded that there is a correlation between the knowledge of Reproductive Health and the occurrence of pruritus vulvae in teenage daughters aged 13-15 years. Suggestion: It is hoped that families can provide basic knowledge related to reproductive health, as well as schools can add books about reproduktive health. Teenagers can also make the best use of the Internet. Keywords: Knowledge; Reproductive Health; Prutitus Vulvae